ANALISIS KANDUNGAN BATANG AKAR MANIS (LICORICE) SEBAGAI UPAYA UNTUK MENGATASI KETERGANTUNGAN SESEORANG PADA ROKOK - Nofiyadi, Nofiyadi (Menara Ilmu, 2020)
Abstract : According to data from the Ministry of Health 2018 the number of active individuals in Indonesia reaches 60 million. This is alarming considering that most of them come from children from the age of 10 years to adolescents aged 18 years. If seen as a whole the number of smokers in Indonesia is 27.6% and if it is analogized from 4 Indonesian residents, 1 of them is a smoker. And thousands of people have died from consuming cigarettes or just as passive smokers, because smoking is the cause of the deadliest disease in the world. If the government has not been able to tackle or close the cigarette factory then the most appropriate effort is to make cigarette consumers stop smoking. One of the efforts is to use liquorice as an alternative in reducing to stop smoking consumption in someone. Santoso research (2017) suggests that the administration of liquorice extract (G. glabra Linn.), Can prevent significantly lowering rat body weight, number and area lesions, gastric damage score, number of mast cells, eucinophil cells in the mucosa and submucosal induced gastric submucosa. This means that if the effect of not smoking is nausea, sweet root will be able to be a deterrent. The purpose of this study is to determine the content of the stem of liquorice to overcome one's dependence on cigarettes, then this study also aims to find out how the impact of cigarette consumption on smokers after being given therapy using liquorice stems. This research method phase is an experimental laboratory through a randomized post test group approach. This means that this research conducted experiments first and then did a quantitative assessment of the impact of this.The data collection method is the chosen sweet root stem which will be tested in the laboratory, the results will be analyzed to find out whether it has to do with reducing the desire to smoke besides the liquorice stem will be tested on selected smokers with a sample of 100 smokers, each respondent will be directed to replace their cigarettes with cinnamon sticks if there is a desire to smoke and the researcher will give a certain time and make an assessment of whether the sweet root sticks influence in overcoming respondents' dependence on cigarettes. The results obtained through laboratory testing can be found that liquorice contains Saponin and Glycyrrhizin and glycyrrhetenic acid. As for the results of the sweet root test to a sample of one hundred people, we get the results: From 100 respondents who were given small pieces of liquorice, which asked each respondent who wanted to smoke first to bite or chew the cut of the sweet root that had been give it. The results are 74 people or 74% of 100 people feel the impact of a decrease in desire to smoke and the remaining 26 people or 26% do not feel any effect. According to respondents the effect if not smoking ie the tongue feels uncomfortable, nausea and coughing feels reduced when biting the liquorice. Keywords: Sweet Root, Cigarette, Licorice